Construction and calibration of a bar weighing lysimeter - Mariano, Daiane de Cinque; Faria, Rogerio Teixeira de [UNESP]; Lourenco de Freitas, Paulo Sergio; Lena, Bruno Patias; Johann, Andre Luiz [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2015)
Generally, standard lysimeters include a lever-load cell scale, which has become expensive compared to new electronic equipment available for experimental purposes. Currently, lysimeters containing weighing bars with up to 4 load cells are economically feasible. This goal of this study was to present the construction and calibration of four weighing lysimeters built using two rectangular tanks, with a surface area of 1.35 m(2) (1 m by 1.35 m) and a depth of 1.5 m, loaded on two weighing bars. Each bar had two high accuracy loading cells connected to a junction box and a datalogger by a coaxial cable. Calibration of each lysimeter was performed after field installation. The results showed a linear response (R-2 > 0.9999) of electric signal (mV) to mass increase or decrease (kg) with minimum hysteresis. The mean absolute error of the mass estimate (0.0245 to 0.2844 equivalent-mm) and a Willmott index between the observed and estimated data (d = 1.0000) indicate the high precision of the new equipment. The results allow concluding that the lysimeters in this study are appropriate for estimating evapotranspiration and other components of soil water balance.
Keywords: evapotranspiration; water balance; soil water